Bone marrow angiogenesis and progression in multiple myeloma: Clinical significance and therapeutic approach - Eleutherakis-Papaiakovou, V.; Karali, M.; Kokkonouzis, I.; Tiliakos, I.; Dimopoulos, M.A. (Leukemia and Lymphoma, 2003)
It is now well established that solid tumors depend on angiogenesis. Promoters and inhibitors of angiogenesis are in balance and antiangiogenic strategies aim at repressing the angiogenic process, thus retarding solid tumor progression. Recent data suggest the importance of angiogenesis in hematologic malignancies and several studies reveal an increased angiogenesis in active multiple myeloma. Angiogenesis seems to be a prominent feature of MM progression, and seems to be correlated with the prognosis and the resistance of MM to chemotherapy. Numerous cell populations and cytokines are involved in angiogenesis in multiple myeloma and antiangiogenic therapy with thalidomide is effective in patients with refractory or relapsed disease. The combination of thalidomide and of other immunomodulatory agents with other therapeutic regimens could lead to more effective management of patients with multiple myeloma.
Keywords: Angiogenesis; Antiangiogenic therapy; multiple myeloma; Thalidomide